Estrategias lúdicas para el cuidado del medio ambiente en estudiantes del quinto ciclo de la Institución Educativa N° 60115 Almirante Miguel Grau Seminario de la Comunidad Nativa Padre Cocha, Iquitos 2024 - Huaynacari Romayna, Miguelina (2025)
The research aimed to explore how play-based strategies can be used as a pedagogical tool to strengthen ecological responsibility in fifth-cycle primary school students. A quantitative approach was adopted, with a quasi-experimental and descriptive design. The sample matched the entire population: 39 students from that cycle. Data collection was carried out through direct observation and questionnaires. The results showed significant progress in the satisfactory achievement level reached by the students. This led to the conclusion that the Play-Based Strategies Program was an effective tool for promoting environmental care, as reflected in the development of environmental awareness and ecological practices among the participants. The proposed hypothesis was statistically confirmed. Spearman's correlation analysis showed a strong positive relationship between the variables (Rho = 0.770), with a very high level of significance (p < 0.001).